Diagnostic accuracy of the RUSH protocol in identifying the cause of shock: a prospective study from an Indian emergency department - Krishna, Mudutanapalli Shiva; Mohammed, Abdurrahman; Koushik, Nanna Varun; Luqman, M. Abdul Muqsith; Reddy, G. Krishna Mohan; M., Noorulla Khan; M., Susheel Kumar; J., Ravikanth (International Journal of Research in Medical Sciences, 2026)
Background: Shock is a life-threatening emergency characterized by inadequate tissue perfusion, requiring rapid identification of the underlying etiology to guide targeted management. Early clinical assessment may be unreliable because of overlapping presentations. The Rapid Ultrasound in Shock and Hypotension (RUSH) protocol provides a structured point-of-care ultrasonography (PoCUS) approach to differentiate shock subtypes at the bedside. To evaluate the diagnostic accuracy of the RUSH protocol in identifying the etiology of non-traumatic undifferentiated shock in an Indian emergency department and to assess its agreement with the final confirmed clinical diagnosis. Methods: This prospective observational study included 100 adult patients presenting with shock to a tertiary emergency department. All patients underwent a standardized RUSH examination performed by trained emergency physicians. Ultrasound-based provisional diagnoses were compared with final diagnoses established using comprehensive clinical evaluation, imaging and laboratory investigations. Diagnostic performance was assessed using sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and Cohen’s kappa coefficient. Results: The mean patient age was 44.97±10.88 years, with a male predominance (69%). Distributive shock was the most common etiology (39%). The RUSH protocol showed the highest diagnostic accuracy for obstructive shock (sensitivity, specificity, PPV and NPV all 100%, κ=1.0). Good agreement was observed for cardiogenic (κ = 0.93), hypovolemic (κ=0.87) and distributive shock (κ=0.87), while overlap was greatest in hypovolemic/distributive shock (κ=0.76). Conclusions: The RUSH protocol is a rapid, reliable bedside tool for early etiological diagnosis of shock and supports timely, goal-directed resuscitation in emergency settings.